Special quasirandom structures for perovskite solid solutions - Jiang, Zhijun; Nahas, Yousra; Xu, Bin; Prosandeev, Sergey; Wang, Dawei; Bellaiche, Laurent (Journal of physics. Condensed matter, 2016)
Special quasirandom structures (SQS) are presently generated for disordered (A′1−xA″x)BX3 and A(B′1−xB″x)X3 perovskite solid solutions, with x  =  1/2 as well as 1/3 and 2/3. These SQS configurations are obtained by imposing that the so-called Cowley parameters are as close to zero as possible for the three nearest neighboring shells. Moreover, these SQS configurations are slightly larger in size than those available in the literature for x  =  1/2, mostly because of the current capabilities of atomistic techniques. They are used here within effective Hamiltonian schemes to predict various properties, which are then compared to those associated with large random supercells, in a variety of compounds, namely (Ba1−xSrx)TiO3, Pb(Zr1−xTix)O3, Pb(Sc0.5Nb0.5)O3, Ba(Zr1−xTix)O3, Pb(Mg1/3Nb2/3)O3 and (Bi1−xNdx)FeO3. It is found that these SQS configurations can reproduce many properties of large random supercells of most of these disordered perovskite alloys, below some finite material-dependent temperature. Examples of these properties are electrical polarization, anti-phase and in-phase octahedral tiltings, antipolar motions, antiferromagnetism, strain, piezoelectric coefficients, dielectric response, specific heat and even the formation of polar nanoregions (PNRs) in some relaxors. Some limitations of these SQS configurations are also pointed out and explained.